Interaction between catechol‐O‐methyltransferase polymorphism and childhood trauma in suicidal ideation of patients with post‐traumatic stress disorder - Kwon, Aeran (Brain Behav, 2020)
INTRODUCTION: Suicidal behavior of post‐traumatic stress disorder (PTSD) patients is influenced by genetic and environmental factors. The catechol‐O‐methyltransferase (COMT) gene has been known to be associated with suicidal ideation. The present study aimed to explore the relationship of COMT polymorphism, childhood trauma, and suicidal ideation in patients with PTSD. METHODS: Fifty patients with PTSD and 62 healthy controls (HCs) were recruited, and COMT variants rs4680 and rs4633 were genotyped through peripheral blood. Psychological assessments such as the childhood trauma questionnaire (CTQ), the scale for suicidal ideation, the clinician‐administered PTSD scale for DSM‐5, and a PTSD checklist were administered. A regression analysis, the Johnson–Neyman technique, and a two‐way analysis of covariance were conducted. RESULTS: Interaction of COMT polymorphism (rs4680, rs4633) and childhood emotional abuse (subscale of CTQ) predicted suicidal ideation in patients with PTSD. Patients with the rs4680 Val/Val genotype, compared to Met carriers genotype, showed higher suicidal ideation when childhood emotional abuse was high. Patients with the rs4633 CC genotype, compared to T carriers genotype, showed higher suicidal ideation when childhood emotional abuse was high. CONCLUSION: Our results suggest that vulnerability to suicide could be increased in the Val/Val genotype of COMT rs4680 and the CC genotype of rs4633 in patients with PTSD. Moreover, PTSD group with high childhood emotional abuse demonstrated a significantly higher suicidal ideation than did those with low childhood emotional abuse.